2017
DOI: 10.3892/ol.2017.6129
|View full text |Cite
|
Sign up to set email alerts
|

Allicin inhibits the invasion of lung adenocarcinoma cells by altering tissue inhibitor of metalloproteinase/matrix metalloproteinase balance via reducing the activity of phosphoinositide 3-kinase/AKT signaling

Abstract: Abstract. Allicin, the main active principle associated with Allium sativum chemistry, has various antitumor activities. However, to the best of our knowledge, there is no available information to address the anti-invasive effect and associated mechanism in lung adenocarcinoma. In the present study, cell viability assay, cell adhesion assay, western blot analysis, Transwell migration and invasion assays and reverse transcription-quantitative polymerase chain reaction were performed. Allicin was identified to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…In the present study, allicin inhibited migration and promoted cell death in the investigated lung and colorectal tumor cell lines [40,44]. The biological effects of allicin are attributed to the thiol groups.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In the present study, allicin inhibited migration and promoted cell death in the investigated lung and colorectal tumor cell lines [40,44]. The biological effects of allicin are attributed to the thiol groups.…”
Section: Discussionsupporting
confidence: 50%
“…Allicin 24h treatment was shown to be efficient in lung, breast, and colon cancer [42], and thyroid cancer [43]. Allicin can inhibit cell the migration and proliferation of lung adenocarcinoma after 24h treatment [40,44]. Furthermore, the 24h co-treatment of allicin combined with 5-FU showed that allicin sensitizes hepatocarcinoma cells to 5-FU, stimulating drug uptake [8].…”
Section: Discussionmentioning
confidence: 99%
“…Allicin is produced from alliin (S-allylcysteine sulfoxide) by the enzyme, alliinase, upon tissue damage (1). Allicin has been shown to possess a variety of beneficial pharmacological and therapeutic effects, such as antimicrobial activity (2,3), anti-tumor effects (4), and the selective reduction of plasma lipid (triacylglycerol and LDL-cholesterol) concentrations (5).…”
mentioning
confidence: 99%
“…For example, Zhang et al suggested 20(S)-protopanaxadiol (PPD) as a promising chemopreventive agent that downregulated the PI3K/Akt signaling pathway in A549 cells [68]. It was also indicated that allicin may inhibit invasion of LUAD by reducing the activity of the PI3K/AKT signaling pathway [69], and baicalein may increase cisplatin sensitivity of A549 cells via the PI3K/Akt/NF-κB pathway [70]. On the other hand, it was reported that mangiferin relieves lipopolysaccharide-induced injury by activating the PI3K/AKT pathway [71].…”
Section: Discussionmentioning
confidence: 99%